Understanding the Path Toward Financial Well-Being: Evidence From India - Sehrawat, Kanchan; Vij, Madhu; Talan, Gaurav (Frontiers in Psychology, 2021)
Many countries are taking steps to establish national strategies to improve the financial well-being (FWB) of their people. However, FWB as a term is still in the infancy stage with a handful of models developed in the context of developed countries. Thus, there is a need to understand FWB from a multi-disciplinary and multi-dimensional approach to draft and implement efficient strategies, especially in the context of developing countries like India. In this study, we have performed path analysis to identify the specific constituents of financial literacy, financial behavior (FinB), and personality traits that affect the FWB (perceived and objective) of an individual in Indian context. Survey responses of 349 respondents are analyzed to empirically validate the proposed relationships using the partial least squares structural equation modeling (PLS-SEM) approach. The analysis mostly provides support to existing literature and challenges some. The findings provide support to 12 out of 17 tested effects with eight hypotheses. The understanding of pathways that lead to increased FWB of individuals has the potential to facilitate effective policy-making and designing of curriculum to support efforts of individuals toward higher FWB and responsible FinBs.